Paciente de sexo femenino de 60 años de edad con diabetes mellitus tipo 2 y esteatosis hepática. - Coloma Yánez, Andrea Michelle (2020)
Hepatic steatosis is one of the most prevalent diseases today. Steatosis is an accumulation or saturation of visceral fat within the liver; This problem arises from poor eating habits or is also associated with dyslipidemia problems, a Body Mass Index greater than 25 kg / m2 and Diabetes Mellitus type II; The current clinical case refers to a sixty-year-old woman from the city of Guayaquil, with a history of Type II Diabetes mellitus 5 years ago on treatment with metformin; You don't refer allergies; Surgical history none. A month ago she was diagnosed with Hepatic Steatosis; He goes to routine control where he indicates that the last days he has presented discomforts among them, headaches, tingling in the feet, blurred vision and imbalance; On normal physical examination without incident; Normal vital signs; The nutritional assessment indicated overweight with increased CVR; Laboratory tests reflected examinations carried out showed hypoglycemia, hypertriglyceridemia, hypercholesterolemia, elevated transaminase, and she was referred to the nutrition service for her intervention. The Individualized Diet Therapeutic Plan that was made to the patient, was based on the current health problems, the type of diet that was prescribed was the Normocaloric Diet, low in saturated fat, high in complex carbohydrates, high in fiber divided into 5 meal times, these include your 3 main meals and your two snacks, bearing in mind that you must choose fats that provide omega 3 and 6 such as polyunsaturated and monounsaturated fatty acids in order to maintain optimal levels of glucose and lipid profile.